Recent Progress in the Growth and Applications of Graphene as a Smart Material: A Review - Aïssa, Brahim; Memon, Nasir K.; Ali, Adnan; Khraisheh, Marwan K. (Frontiers in Materials, 2015)
Innovative breakthroughs in fundamental research and industrial applications of graphene material have made its mass and low-cost production a necessary step toward its real world applications. This one-atom thick crystal of carbon, gathers a set of unique physico-chemical properties, ranging from its extreme mechanical behavior to its exceptional electrical and thermal conductivities, which are making graphene as a serious alternative to replace many conventional materials for various applications. In this review paper, we highlight the most important experimental results on the synthesis of graphene material, its emerging properties with reference to its smart applications. We discuss the possibility to successfully integrating graphene directly into device, enabling thereby the realization of a wide range of applications, including actuation, photovoltaic, thermoelectricity, shape memory, self-healing, electrorheology and space missions. The future outlook of graphene is also considered and discussed.